Genetic characterization and phylogenetic analysis of infectious bursal disease virus from commercial broiler flocks in the Philippines - Atienza, Mark Lawrence G. (The Philippine Journal of Veterinary Medicine, 2022)
Infectious bursal disease (IBD) is a highly contagious immunosuppressive disease of poultry. To better understand the epidemiology of IBD virus (IBDV) in the country, a total of 39 field IBDVs from commercial broiler flocks in seven regions of the Philippines were analyzed. Clinical signs observed were uniformity problems, inappetence, lethargy, stunted growth, poor average daily gain, irregular size of bursa of Fabricius, and mortality rates ranging from four to 19%. Phylogenetic analysis highlighted the following: three (7.69%) field strains were from G1 classic genotype; 16 (41.03%) were G1 vaccine IBDVs; 17 (43.59%) were G2 variants; two (5.12%) were G3 vvIBDVs; and one (2.56%) was a G7 vaccine IBDV. Regional distribution showed that G1 IBDVs were detected in regions 2, 3, 4, 5, 6, 7, and 11, G2 IBDVs were observed in Regions 3 and 4, G3 IBDVs in Regions 6 and 7, and G7 IBDV in Region 3. It was demonstrated that G2 IBDVs were closely related (95-96%) to variant strains from the USA, whereas the G1 and G3 IBDVs were closely related (96.00-100%) to IBDVs from several countries in Southeast and Far East Asia. This study is so far the first to comprehensively document the molecular as well as the epidemiological characteristics of IBDVs in the Philippines.